Factors affecting the use of malaria prevention methods among pregnant women in Kenya. - Choonara, Shakira (My University, 2013)
Abstract Background In sub-Saharan Africa, malaria is the leading cause of morbidity and mortality. An estimated 15 million malaria cases and 40 000 malaria deaths were reported in Kenya. Malaria during pregnancy is associated with adverse health outcomes for both the mother as well as her foetus. The purpose of this study was to examine the relationship between socioeconomic correlates and the uptake of malaria prevention methods during pregnancy. Methodology: Data was drawn from the 2008-2009 Kenya Demographic and Health Survey. A total of 8098 women aged 15-49 were analysed. Stata version 12 was used for the management and analysis of data. Univariate, bivariate and multivariate analysis was carried out to meet the objectives of this study. Results: Forty-eight percent of women made use of Insecticide Treated Net (ITNs), 52 percent were administered with Intermittent Preventative Therapy (IPTp) and 36 percent made use of both measures during pregnancy. Multivariate results indicate that urban women were found to display slightly higher odds of ITN usage (1.13) and the combined usage of ITNs and IPTp (1.22) during pregnancy in comparison to rural women. Women with higher levels of education and women from middle income and rich households displayed higher odds of the uptake of these malaria prevention methods during pregnancy. Conclusion: This study has shown that socioeconomic indicators influence the usage of malaria prevention methods during pregnancy. It is therefore imperative that these factors be considered when designing and implementing policies aimed at improving the uptake of these measures during pregnancy.
Keywords: Pregnant women--Health and hygiene--Kenya.; Malaria--Kenya--Prevention.